When Bureaucracy is Literature: the literariness in the reports of Graciliano Ramos - Adreana Dulcina Platt; Ubaldo César Balthazar; Frederico Augusto Garcia Fernandes (Universidade Federal do Rio Grande do Sul, 2019)
This study is in the realm of the pedagogical use of literary expression that identifies literary aspects in historical narratives. We deal with the concept of literariness in the reports of Mayor Graciliano Ramos between 1929 and 1930. The historical rescue of the administrative routine reveals how the literary education of the author emerges in a poetic reality and objectivity despite of its bureaucratic nature. This article discusses the basic principals of the municipal public function under the aegis of the Constitution of 1891, in a way to identify the literary and stylistic resistance of the author. We then consider some aspects such as: verisimilitude, allegory, metaphors, and irony presented in the reports, which demonstrate the pedagogical virtues of a literary text.